Is anterior cervical discectomy and fusion superior to corpectomy and fusion for treatment of multilevel cervical spondylotic myelopathy? A systemic review and meta-analysis. - Ying-Chao Han; Zhu-Qing Liu; Shan-Jin Wang; Li-Jun Li; Jun Tan (PLoS ONE)
Objective Both anterior cervical discectomy with fusion (ACDF) and anterior cervical corpectomy with fusion (ACCF) are used to treat cervical spondylotic myelopathy (CSM), however, there is considerable controversy as to whether ACDF or ACCF is the optimal treatment for this condition. To compare the clinical outcomes, complications, and surgical trauma between ACDF and ACCF for the treatment of CSM, we conducted a meta-analysis. Methods We conducted a comprehensive search in MEDLINE, EMBASE, PubMed, Google Scholar and Cochrane databases, searching for relevant controlled trials up to July 2013 that compared ACDF and ACCF for the treatment of CSM. We performed title and abstract screening and full-text screening independently and in duplicate. A random effects model was used for heterogeneous data; otherwise, a fixed effect model was used to pool data, using mean difference (MD) for continuous outcomes and odds ratio (OR) for dichotomous outcomes. Results Of 2157 citations examined, 15 articles representing 1372 participants were eligible. Overall, there were significant differences between the two treatment groups for hospital stay (M = -5.60, 95% CI = -7.09 to -4.11), blood loss (MD = -151.35, 95% CI = -253.22 to -49.48), complications (OR = 0.50, 95% CI = 0.35 to 0.73) and increased lordosis of C2-C7 (MD = 3.70, 95% CI = 0.96 to 6.45) and fusion segments angles (MD = 3.38, 95% CI = 2.54 to 4.22). However, there were no significant differences in the operation time (MD = -9.34, 95% CI = -42.99 to 24.31), JOA (MD = 0.24, 95% CI = -0.10 to 0.57), VAS (MD = -0.06, 95% CI = -0.81 to 0.70), NDI (MD = -1.37, 95% CI  = -3.17 to 0.43), Odom criteria (OR = 0.88, 95% CI = 0.60 to 1.30) or fusion rate (OR = 1.17, 95% CI = 0.34 to 4.11). Conclusions Based on this meta-analysis, although complications and increased lordosis are significantly better in the ACDF group, there is no strong evidence to support the routine use of ACDF over ACCF in CSM.